Proceeding: The 2nd International Conference of Medical and Health Sciences (ICMHS) and The 2nd Life Sciences Conference (LSC) 2016 - Tri Wahyuliati, Muhammad Sasmito Djati, dkk (UMY, 2016)
Proceeding: The 2nd International Conference of Medical and Health Sciences (ICMHS) and The 2nd Life Sciences Conference (LSC) 2016